Analisis Yuridis Tindak Pidana Korupsi dengan Menggunakan Jabatan (Studi Putusan No. 296/Pid.B/2010/PN.Mdn) - Muhammad Iqbal Mas'ud Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
The purpose of this research is to know the regulation of criminal law in corruption crime by using position; the juridical analysis of corruption crime by using position with decision no. 3296 / Pid.B / 2010 / PN.Mdn. This type of thesis research uses qualitative research, using normative juridical research. The research method used, namely library research (library research) and field study (field research) with the location of research at the Medan District Court. Data collection techniques used are secondary data, consisting of primary, secondary and tertiary legal materials. The legal basis for the eradication of criminal acts of corruption is contained in Law No. 20 of 2001 on Amendment to Law Number 31 Year 1999 on the Eradication of Corruption. The consideration of the Panel of Judges of the Medan District Court in deciding the case has used juridical judgment based on juridical facts. Which have been revealed in the hearing and by the Law stipulated as matters which must be contained in the decision such as the indictment of the prosecutor, the statement of the defendant, witness testimony, Evidence items, and articles in criminal law. Based on the Medan District Court Ruling. 3296 / Pid.B / 2010 / PN.Mdn, proves that the defendant is not proven to abuse the authority, opportunity or means available to him / her because of his / her position or position as the person in charge of the team which aims to benefit yourself, others or as a corporation.